Solving polynomial equation systems. - Mora, Teo (Encyclopedia of mathematics and its applications, 2003)
Mora covers the classical theory of finding roots of a univariate polynomial, emphasising computational aspects. He shows that solving a polynomial equation really means finding algorithms that help one manipulate roots rather than simply computing them; to that end he also surveys algorithms for factorizing univariate polynomials.